2012
DOI: 10.5888/pcd9.120023
|View full text |Cite
|
Sign up to set email alerts
|

Small Food Stores and Availability of Nutritious Foods: A Comparison of Database and In-Store Measures, Northern California, 2009

Abstract: IntroductionSmall food stores are prevalent in urban neighborhoods, but the availability of nutritious food at such stores is not well known. The objective of this study was to determine whether data from 3 sources would yield a single, homogenous, healthful food store category that can be used to accurately characterize community nutrition environments for public health research.MethodsWe conducted in-store surveys in 2009 on store type and the availability of nutritious food in a sample of nonchain food stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Similarly, studies have found that the availability of convenience stores increases the walkability of a neighborhood , which has been associated with lower obesity . Additionally, there is evidence that access to unhealthy foods is ubiquitous in the US , making it impossible to see differences in associations with obesity at current exposure levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies have found that the availability of convenience stores increases the walkability of a neighborhood , which has been associated with lower obesity . Additionally, there is evidence that access to unhealthy foods is ubiquitous in the US , making it impossible to see differences in associations with obesity at current exposure levels.…”
Section: Discussionmentioning
confidence: 99%
“…The main weakness of Business Analyst identified by Forsyth et al (2010) was in coding businesses by type, but as the study team coded fast food restaurants using names this issue was minimized. Others have pointed out that fieldwork is superior to commercial business databases in assessing the nutrition level of food in food stores (such as convenience and grocery stores) where availability of different food types varies across stores (Kersten et al, 2012). This is also a problem with restaurants, though in the case of fast food restaurants there is presumably more uniformity of food types across facilities.…”
Section: Methodsmentioning
confidence: 99%
“…Smaller community and neighborhood retail food venues may exert a greater influence on the acquisition of household food supplies [15,16], especially for limited resource families in rural/underserved areas [3,17]. Neighborhood food stores, such as convenience stores, are ubiquitous, smaller in size and carry fewer fresh and healthier food items [3,18-20]. …”
Section: Introductionmentioning
confidence: 99%